Motivasi Masyarakat Kota Makassar Melakukan Transaksi Melalui E-Commerce - Fatmawati, Fatmawati (LAA MAISYIR : Jurnal Ekonomi Islam, 2020)
This study aims to see the motivation of the Makassar people to transact through e-commerce. The transaction model is relatively new in society, but has become a trend of its own and is so desirable in almost every circle of society. This research is a descriptive qualitative field research conducted in Makassar using a normative theological, phenomenological and Islamic economic approach. The results of this study indicate that transaction motivation through E-commerce consists of rational motivation, that is motivation that occurs due to careful consideration of consumers before deciding to transact and emotional motivation, namely the spontaneous motivation to emerge when seeing unique or interesting items, as well as in conventional transactions. The difference is that in an e-commerce transaction, the community will get value added or added value in the form of "excellent services" or excellent services because of the various facilities available in e-commerce so that the community will feel pampered in the transaction.